UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL EMBELAJARAN MAKE A MATCH BERBANTUAN MEDIA GAMBAR PADA SISWA KELAS V SDN 3 SUKAJAWA BANDAR LAMPUNG TAHUN PELAJARAN 2018/2019 - Rohelyati Rohelyati (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
This Classroom Action Research was conducted in January - March at even semester of the 2018/2019 academic year. The background of the problem in this study is the low learning achievement of grade V students of SDN 3 Sukajawa in the 2018/2019 academic year. The formulation of the problem of this research is how to improve the results of science learning through the Make A Match learning model in class V SDN 3 Sukajawa Bandar Lampung in the academic year 2018/2019. The problem solving in this research is to use Make A Match learning model. The purpose of this study was to improve the quality of science learning through the Make A Match model in class V SDN 3 Sukajawa Bandar Lampung. The research design used three cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. The research subjects were fifth grade students of SDN 3 Sukajawa Bandar Lampung. Data collection techniques using observation and tests. In the first cycle, the average score of teacher skills was 2.8 with good categories, the percentage value of student activity was 58.6%, the average value of student learning achievement was 56.67 and learning completeness was 58.3%. In the second cycle, the average value of teacher skills was 34 with good categories, the percentage value of student activity was 64.8%, the average value of student learning achievement was 67.22 and learning completeness was 72.2%. Whereas in cycle III the average score of teacher skills was 3.9 with good category, the percentage value of student activity was 76.9%, the average value of student learning achievement was 75.28 and learning completeness was 88.89%